Assessing perception of mattering in a cross-cultural university context: validity and reliability of the Italian and Hungarian versions of the University Mattering Scale (UM-S) - Matera, Camilla; Papp, Zsuzsanna Katalin; Paradisi, Monica; Pieri, Chiara; Catling, Jonathan; Nerini, Amanda (Frontiers in Psychology, 2024)
The present study aimed to gather evidence on the validity and reliability of the Italian and Hungarian versions of the University Mattering Scale (UM-S). This 10-item scale assesses university students’ perceptions of mattering across three dimensions: Awareness, Importance, and Reliance. University students from Italy (n = 210) and Hungary (n = 191) completed a questionnaire that included the adapted UM-S, along with measures of societal mattering, social support, well-being, and academic self-efficacy. A confirmatory factor analysis (CFA) supported the three-factor structure of the scale in both contexts. The scale demonstrated high internal consistency, providing evidence of its reliability. Consistent with the original version, both the Italian and Hungarian UM-S showed good discriminant and convergent validity, as evidenced by its association with instruments measuring perceived social support and societal mattering. Additionally, the scale showed strong criterion-related and incremental validity; university mattering significantly predicted students’ well-being and academic self-efficacy, even after controlling for perceived social support. Furthermore, the scale was partially invariant across countries at the scalar level. A comparison of UM-S scores between the two groups revealed that Hungarian students perceived higher levels of university mattering than their Italian counterparts. In conclusion, the Italian and Hungarian versions of the UM-S are appropriate for use in academic contexts to assess students’ sense of being valued by their university. The instrument, having been shown to be both valid and reliable, is suitable for both research and intervention purposes.